Manejo integrado del mal rosado (Corticium salmonicolor Berk. y Br.), en el cultivo de café. - Guanoluiza Beltrán, Cesar Augusto (2024)
Coffee originated in Ethiopia and spread to Arabia in the 12th century. Later, it reached Europe and was taken to the colonies of America, becoming an important commodity in South America. In Ecuador, coffee cultivation is one of the main non-oil export products and has experienced an increase in recent years. However, Ecuadorian coffee farming faces challenges such as aging coffee plantations, quality and safety issues, and the incidence of diseases affecting production. This document aims to provide information and training to farmers to improve coffee production and promote coffee farming development in Ecuador. Integrated management of pink disease is essential to prevent and control this disease and improve coffee farmers' yields. Through practices such as pruning, bush cleaning, and preventive spraying, farmers can ensure sustainable, efficient, and high-quality production. This literature review will provide farmers with the necessary insights to manage pink disease in coffee cultivation and achieve their production goals. The fungus Corticium salmonicolor is known as the cause of "pink disease," which affects woody plantations such as acacia, rubber, eucalyptus, and some fruit trees, as well as tropical crops like cocoa, coffee, tea, ramie, and rubber. This disease is characterized by white mycelial growth that extends, forming a web-like network, followed by the formation of cottony-looking sclerotia. Affected plants show yellowing leaves and symptoms of wilting and defoliation, and in severe cases, can lead to the downward death of the plant. To control this disease and prevent its spread, reducing planting density, removing affected branches, regulating shade, using entomopathogenic fungi such as Trichoderma spp. and Verticillium lecanii, and applying copper oxychloride products are recommended. It is important to note that pink disease may interact with other coffee pests and diseases, thus requiring an integrated approach to address multiple issues simultaneously.